Microscopic and macroscopic measurements of emphysema: relation to carbon monoxide gas transfer. Issue 3 (March 1992) - McLean, A; Warren, P M; Gillooly, M; MacNee, W; Lamb, D
Abstract : BACKGROUND: Studies of the relation between the severity of structural change in emphysema and physiological abnormality have been based on macroscopic assessments, which have not been truly quantitative or sensitive enough to detect early changes. With a highly reproducible method for measuring emphysema using histological sections and a semiautomatic image analysis system, this quantitative assessment of emphysema was compared with a semiquantitative macroscopic assessment of emphysema and measurements of carbon monoxide gas transfer. METHODS: Microscopic and macroscopic measurements of emphysema on 44 thoracotomy specimens were compared; only two were from non-smokers. Airspace wall surface area per unit volume was measured microscopically with an automatic image analyser and expressed as both the mean airspace wall surface area per unit volume and the mean value of the five fields with the lowest values. Macroscopic emphysema was measured directly on a tracing of the midsagittal slice using a digitising tablet attached to a microcomputer and expressed as a percentage of the total area of lung. In cases with centriacinar emphysema the number of discrete lesions was counted. RESULTS: The area of macroscopic emphysema ranged from 0 to 78% of the total area of lung examined, but most patients had less than 1% involvement so that the distribution was highly skewed. Both mean airspace wall surface area per unit volume and the mean of five fields with the lowest airspace wall surface area per unit volume were normally distributed, with mean airspace areas ranging from 8.8 to 25.4 mm2/mm3 (mean 18.1 mm2/mm3). In lobes with centriacinar emphysema the number of discrete lesions correlated with airspace wall surface area per unit volume and with preoperative carbon monoxide transfer factor (TLCO) per unit lung volume. However, other measurements of macroscopic emphysema did not correlate with loss of alveolar wall surface area, and there was considerable overlap between subjects with no or minimal macroscopic emphysema and those with more severe disease. TLCO correlated with both mean airspace wall surface area per unit volume and the mean of five fields with the lowest airspace wall surface area per unit volume but not with the severity of macroscopic emphysema. CONCLUSION: If emphysema is to be quantified it must be measured microscopically; macroscopic measurements do not, in general, reflect the microscopic loss of airspace wall.